The Effect of Angiotensin-Converting Enzyme GenePolymorphism and Angiotensin II Levels in Coronary SlowFlow Phenomenon at Mohammad Hoesin General HospitalPalembang - Karlina, Arlis; Indrajaya, Taufik; Ghanie, Ali; Sukandi, Erwin; Usnizar, Ferry; Indra, Syamsu; Chodilawati, Rukiah; Saleh, Imran (Jurnal Penyakit Dalam Indonesia, 2021)
Introduction. The presence of ACE gene polymorphism is expected to have a role in cardiovascular diseases, including coronary slow flow phenomenon (CSFP). Angiotensin converting enzyme (ACE) gene polymorphism also plays an essential role in increasing angiotensin II levels. Therefore, this study aimed to analyze the effect of angiotensin-converting enzyme gene polymorphism and angiotensin II levels in the coronary slow flow phenomenon in Mohammad Hoesin General Hospital Palembang. Methods. This case-control study was started from July 2019 to July 2020 at RSMH Palembang with 32 subjects for each case (CSFP patients) and the control group (non-CSF patients). This study used a pair of primers and onetimed PCR to detect ACE gene polymorphism. Genetic analysis was carried out in the Biotechnology Laboratory Faculty of Medicine, Universitas Sriwijaya. Statistical analysis was performed using the Spearman correlation test. Results. There were 17 subjects with II genotypes (53.1%), 14 subjects with ID genotypes (43.8%), and 1 subject with DD genotypes (3.1 %) in the CSFP group. While in the non-CSFP group, there were 11 subjects with II genotypes (34.4%), 13 subjects with ID genotypes (42.2%), and 9 subjects with DD genotypes (14.1%). The median value of angiotensin II levels in CSFP and Non-CSF group was 58 pg/mL and 32.8 pg/mL, respectively. The results of the analysis showed that there was an effect of angiotensin II levels on the incidence of CSFP (p=0.001). Further analysis showed that there was a correlation between angiotensin II levels and the I/D 287 bp alu repetitive sequence polymorphism in the intron 16 ACE gene (p=0.030, r=0.822). Conclusions. There was a correlation between I/D 287 bp alu repetitive sequence polymorphism in the intron 16 ACE gene and angiotensin II levels in the coronary slow flow phenomenon at Mohammad Hoesin General Hospital Palembang.